Bioinspired multistructured paper microfluidics for POCT. Issue 21 (7th October 2019) - Gao, Bingbing; Yang, Yaqiong; Liao, Junlong; He, Bingfang; Liu, Hong
Abstract : Multistructured papers (MSPs) with ordered micropillars and colloidal crystal structures were used for fabricating pumpless liquid transport and fluorescence and chemiluminescence (CL) enhancement microfluidic chips for POCT. Abstract : The rapid development of and the large market for medical diagnostics necessitate point-of-care testing (POCT) with superior sensitivity, miniaturization, multiple functionalities and high integration. Thus, flexible substrates with complex structures that provide multiple functions are in demand. Herein, we present multistructured pseudo-papers (MSPs) as a platform for building flexible microfluidics. Flexible and freestanding MSPs are generated by the self-assembly of colloidal silica crystals or core–shell copolymer elastic colloidal crystals on microcavity PDMS molds to form photonic crystals (PCs). Nitrocellulose (NC) multistructured pseudo-papers (NC MSPs) were obtained by etching SiO2 PCs after NC precursor infiltration, while elastic copolymer (EC) multistructured pseudo-papers (EC MSPs) were directly peeled off the mold; both types of freestanding MSPs have ordered micropillars and nanocrystal structures and presented unique properties such as pumpless liquid transport and fluorescence and chemiluminescence (CL) enhancement. MSPs with designed patterns were fabricated by patterned PDMS molds, and complicated microfluidic chips were used to generate MSPs by utilizing these patterns as liquid channels. The MSPs were used for fabricating microfluidic sensors for human cardiac marker and cancer marker sensing; the features of these bioinspired MSPs indicate their potential for sensitive sensing, which will enable them to find broader applications in many fields.